Adverse effects of maternal age, weight and smoking during pregnancy in Pleven, Bulgaria - Kamburova, Mariela Stefanova; Hristova, Petkana Angelova; Georgieva, Stela Ludmilova; Khan, Azhar (South Eastern European Journal of Public Health (SEEJPH), 2015)
Aim: This paper aims to study the relationship between mothers’ age, body mass index (BMI), gestational weight gain (GWG) and smoking and the risk for premature birth in Pleven, Bulgaria. Methods: A case-control study was conducted in Pleven in 2007. The study was comprehensive for all premature children (N=58) and representative for full-term infants (N=192, or 10.4% of all of the 1827 full-term children) born in 2007 at the University Hospital of Pleven and resident in the city of Pleven. Retrospective data on determinants under study were collected from all the mothers included in this study (N=250). Results: Mothers of premature children were more likely to be above 35 years old (27.6%), with a BMI ≥25 kg/m2 (23.1%), GWG below the recommended value (38.5%) and to smoke during pregnancy (37.9%). The odds of being a smoker during pregnancy were five times higher among mothers with low birth weight (LBW) newborns compared with their counterparts with normal birth weight newborns (OR=5.1, 95%CI=2.4-10.6). There was a positive association between BMI and LBW in infants whose mothers were overweight (OR=2.1, 95%CI=1.0-4.0). The risk of LBW increased when GWG was less than recommended (OR=1.8, 95%CI=1.0-3.1). Conclusion: Our results indicate that pre-pregnancy BMI ≥25 kg/m2, less than recommended GWG and smoking during pregnancy are risk factors for premature birth in Pleven region. Findings from this study suggest the need for active health and educational actions by health professionals in order to avoid premature births in Bulgaria.